Modern Interpretation of Creativity in Science - Ruxshona Yunusovna, Musinova (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the psychological definition, essence of creative activity. Differencesas similaritiesbetween creative activity and creative thinking are studied